2021
DOI: 10.2147/ijgm.s301141
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Gut-Muscle Axis and Sarcopenia: The Potential Role of Gut Microbiota

Abstract: Sarcopenia is a multifactorial disease related to aging, chronic inflammation, insufficient nutrition, and physical inactivity. Previous studies have suggested that there is a relationship between sarcopenia and gut microbiota,namely, the gut-muscle axis. The present review highlights that the gut microbiota can affect muscle mass and muscle function from inflammation and immunity,substance and energy metabolism, endocrine and insulin sensitivity, etc., directly or indirectly establishing a connection with sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 100 publications
0
43
0
1
Order By: Relevance
“…Over recent years, probiotics have been used in athletes because of their improved performance and reduced fatigue after exercise [ 128 ]. Animal studies employing mice showed that 4-week supplementation of Lactobacillus salivarius could significantly improve muscle strength and endurance, increase liver and muscle glycogen storage, and acid kinase after exercise [ 129 ].…”
Section: Pathomechanism Of Changes In Skeletal Muscle In Sarcopenia and Sarcopenic Obesitymentioning
confidence: 99%
“…Over recent years, probiotics have been used in athletes because of their improved performance and reduced fatigue after exercise [ 128 ]. Animal studies employing mice showed that 4-week supplementation of Lactobacillus salivarius could significantly improve muscle strength and endurance, increase liver and muscle glycogen storage, and acid kinase after exercise [ 129 ].…”
Section: Pathomechanism Of Changes In Skeletal Muscle In Sarcopenia and Sarcopenic Obesitymentioning
confidence: 99%
“…This was demonstrated by a metagenomic (16S DNA) analysis of stool samples from elite athletes before and after running a marathon. After running, the most remarkable difference was a substantial increase in species of the Veillonella genus, which metabolize lactate into acetate and propionate [84]. A similar study in Olympic rowers found that the relative abundance of butyrate-producing bacteria increased, and insulin sensitivity was improved after prolonged rowing [82].…”
Section: Gut Microbiota Sarcopenia and Gut-muscle Axismentioning
confidence: 85%
“…Nay et al [17], also found that eliminating the gut bacteria using antibiotics impairs muscle function and endurance, partly due to muscle glycogen depletion [17]. It has also been shown that elite athletes increase both microbial diversity and abundance during extreme exercise [81] but mainly increase bacteria-produced SCFA [81][82][83][84]. This was demonstrated by a metagenomic (16S DNA) analysis of stool samples from elite athletes before and after running a marathon.…”
Section: Gut Microbiota Sarcopenia and Gut-muscle Axismentioning
confidence: 95%
“…As time goes by, this makes the body weaker and more susceptible to various diseases [ 14 ]. However, there is an increasing awareness of the relationship between the initial gut microbiota and human health, especially the role of the gut–muscle axis, which plays an important role in exercise performance amongst the elderly [ 15 ]. The structure of the gut microbiota changes through factors such as age, diet, antibiotic intake, disease, and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Its imbalance is closely related to human health and disease and is considered to be a possible determinant of healthy aging [ 16 ]. On the other hand, it can regulate the pathophysiology of age-related sarcopenia through various mechanisms (such as inflammation and immunity, material and energy metabolism, endocrine, and insulin sensitivity), and regulate chronic inflammation and anabolic pathways to directly or indirectly affect muscle mass and function, so as to achieve the optimal “gut–muscle axis” [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%